Empowering Communities Through Sapta Pesona to Enhance Tourism Service Quality in Candi Belahan Village - Khofifah; Hasan Bashori; Muchamad Syarief Hidayatulloh; Izzatul Muflihah; Sucipto (Amalee: Indonesian Journal of Community Research and Engagement, 2025)
Candi Belahan Village in Gempol District, Pasuruan Regency, possesses unique historical and cultural tourism potential that remains underutilized due to limited community awareness of tourism service standards. This community service program aimed to empower local tourism actors by implementing Sapta Pesona principles—safety, orderliness, cleanliness, coolness, beauty, friendliness, and memorable experiences—to enhance the quality of tourism services and strengthen destination management. The program was conducted from July to August 2025, utilizing a participatory training and mentoring approach that involved 30 local participants, including members of the Tourism Awareness Group (Pokdarwis), traders, and local guides. Activities consisted of preliminary assessment, training, field mentoring, and evaluation to encourage behavioral and environmental transformation. The results indicated a substantial increase in participants’ understanding and application of Sapta Pesona, with post-training assessments showing marked improvement in knowledge and service practices, along with enhanced cleanliness, orderliness, and the development of thematic photo spots reflecting local identity. Collaboration between the community, Pokdarwis, and the village government strengthened collective ownership and coordination in managing the tourism area. Overall, the program not only improved tourism service quality but also demonstrated a replicable model for community-based tourism development that may inform broader village tourism policies and future capacity-building initiatives.